Divorcing the dow : - Troup, Jim (John Wiley & Sons, Inc, 2003)
Troup and Michalsky provide investors with a new framework for thinking about financial markets and give specific investment techniques to anticipate the market’s direction and identify companies poised for sustained productivity and long-term growth. Based on in-depth research and field-tested in the authors’ own successful management of millions of dollars in personal and corporate assets, Divorcing the Dow introduces you to a revolutionary paradigm for predicting market patterns. Troup and Michalsky provide you with the state-of-the-art tools needed to make strategic and profitable investment decisions and get a jump-start on other investors who continue to use an investing system that clearly has run its course.